Real-World Study of Adding Bevacizumab to Chemotherapy for Ovarian, Tubal, and Peritoneal Cancer as Front-Line or Relapse Therapy (ROBOT): 8-Year Experience - Wu, Pei-Ying; Cheng, Ya-Min; Shen, Meng-Ru; Chen, Yi-Chun; Huang, Yu-Fang; Chou, Cheng-Yang (Frontiers in Oncology, 2020)
This study aimed to determine the real-world, long-term prognostic impacts and adverse effects (AEs) of bevacizumab (BEV) in Asian patients with ovarian/tubal/peritoneal cancers. We retrospectively reviewed the medical records of consecutive patients with ovarian/tubal/peritoneal cancer on front-line chemotherapy with or without BEV (Cohort 1) and those who relapsed following chemotherapy and/or BEV (Cohort 2) between 2011 and 2018 in a tertiary medical centre. Patient characteristics, BEV dosages, clinical outcomes, and AEs were analysed. Hazard ratios for disease progression and death were analysed using a cox proportional regression model. Benefits of BEV used throughout triweekly, in terms of improved progression-free survival (PFS) and overall survival (OS), were observed at a dosage of 7.5–15 mg/kg among advanced-stage Cohort 1 patients. A progression-free interval of <6 months was the strongest predictor of disease progression and death in advanced-stage patients. BEV throughout and optimal cytoreduction were independent predictors of reduced disease progression. No prognostic advantage was observed between serous and clear cell histologies when BEV was added. Moreover, BEV resulted in improved OS in Cohort 2 patients, especially in the platinum-sensitive subgroup. Most patients had a front-line BEV dosage <10 mg/kg per cycle with <10 treatment cycles. Low rates and grades of BEV-related AEs were observed in both cohorts. BEV used throughout effectively extended PFS and OS in advanced-stage patients with ovarian/tubal/peritoneal cancer. Patients with platinum-sensitive carcinoma, treated with BEV, had a significant improvement in OS and extended PFS. Therefore, BEV can safely be added to chemotherapy for ovarian/tubal/peritoneal cancers.